Math Teachers in Bone Regency Middle Schools: A Profile of Their Differentiated Learning Abilities - Rahma Hidayati Darwis; Suradi Tahmir; Ahmad Talib (AL-ISHLAH: Jurnal Pendidikan, 2024)
Differentiated learning is an instructional approach that prioritizes adapting to the unique needs and characteristics of each student. This study aims to elucidate educators' comprehension and implementation of differentiated learning within an autonomous curriculum framework, focusing on middle school math teachers in Bone Regency. Conducted as a mixed-methods descriptive study, data were collected through a structured academic survey targeting a representative sample of teachers from various middle schools in the region. Quantitative data were statistically analyzed to assess the prevalence of differentiated learning practices, while qualitative data were analyzed thematically to explore common themes and insights regarding teachers' perceptions and challenges. The findings indicate that teachers generally have a limited understanding of differentiated learning. Only 31% of the participants reported designing and implementing differentiated learning strategies, highlighting a significant gap in the application of this instructional approach within the curriculum. The study reveals a critical need for enhanced professional development and support for middle school math teachers in Bone Regency regarding differentiated learning. The limited understanding and implementation of differentiated learning strategies underscore the necessity for targeted training programs and resources to better equip teachers in addressing the diverse needs of their students. By fostering a deeper comprehension and more widespread application of differentiated learning, educational outcomes can be significantly improved within the autonomous curriculum framework.